Plan de negocio para la creación de una empresa productora y comercializadora de helados saludables a base de la semilla de chía en la ciudad de Loja - Cuje Cordero, Delia María (2023)
The Curricular Integration work was based on a "Business Plan for the creation of a company that produces and markets healthy ice cream based on chia seeds in the city of Loja" because in Ecuador, 90% of the enterprises do not reach 3 years due to a lack of innovation and not making a business plan. For this reason, the model of the authors Longenecker, Moore and Petty were used in this work. It was descriptive and exploratory research; the survey and observation were used to collect information. The segment chosen was people from 16 to 59 years of age in the city of Loja with a population of 127,426, obtaining a sample of 384 people. In the first part, the philosophical basis was established, the demand was determined in the marketing plan, and competitive prices were achieved. These are: lt of ice cream at $13.99; 1⁄2 liter at $7.00; and the 125ml staff at $1.75; the point of sale will be the company's premises. In the operations plan, it was established that the size would be 60 liters per day; in the administrative plan, it was possible to determine the nature of the company, which will be a limited company; its organization chart and manual of functions for 6 jobs was established; in the financial plan it was known that $45,211.83 is required to start up the business, in the first year of operation, a profit of $48,603.43 dollars is planned; and in the cash flow, it produces positive flows in the 5 years of the project's life. From the economic- financial point of view, it has an evaluation of IRR=35.11% and NPV=$28,094.49 dollars, which is positive. Therefore, the implementation of this new company in the city of Loja is recommended.